THE STRATEGIES OF SERVICE QUALITIY AT THE HOSPITAL TYPE D (OTANAHA HOSPITAL) OF GORONTALO CITY - Titin Dunggio; Lisda Van Gobel; Yanti Mustafa (LP2M Universitas Bina Mandiri Gorontalo, 2021)
This research was conducted with the aim of: 1) knowing and analyzing the strategy for improving the quality of services at Otanaha Hospital; 2) to identify and analyze the factors that determine the strategy for improving the quality of services at the Otanaha Hospital. This study uses a descriptive qualitative approach with data collection techniques through observation and interviews and documentation. 9 informants included: KTU representing Directors, Doctors and Nurses, who are at the Otanaha Regional General Hospital, this research was conducted from June to July 2020. The results showed that: 1) the strategy to improve the quality of services at Otanaha Hospital only applies two strategies, namely the organizational strategy and the program strategy that emphasizes the vision aspects of the hospital; 2) factors that determine the improvement of service quality at the Otanaha Regional Hospital include the lack of human resources in terms of quality and quantity, limited facilities and infrastructure that are not yet as planned. It is recommended: 1) the hospital continues to strive to develop human resources through training or technical guidance; 2) it is necessary to increase and develop facilities and infrastructure for the realization of the expected service quality.